PENGARUH SUKU BUNGA, LIKUIDITAS DAN MATURITY TERHADAP HARGA OBLIGASI KORPORASI DI BURSA EFEK INDONESIA - Silalahi, Donalson; Ndruru, Devi Sartika (Jurnal Manajemen dan Bisnis, 2024)
This research aims to determine and explain the influence of interest rates, liquidity and maturity on corporate bond prices on the Indonesian Stock Exchange. This research was conducted on bonds on the Indonesian Stock Exchange with the research period covering the 1st quarter to the 4th quarter of 2020-2022. The population in this study was 705 bond codes, and the sample used was 38 bond codes selected using a purposive sampling method so that 456 observation data were obtained. The analysis technique used in this research is multiple linear regression. The research results show that the interest rate has a negative and significant effect on bond prices with a linear regression coefficient of -2.356 and a significance value of 0.000. Liquidity (trading volume) has an insignificant influence on bond prices with a linear regression coefficient of -0.001 and a significance value of 0.456. Meanwhile, maturity (remaining life) has a positive and significant effect on bond prices with a linear regression coefficient of 0.283 and a significance value of 0.000.